Rhetoric Versus Reality – Embedding a New Relationship Within Integrated Care Systems for Third Sector Organisations - Christopher Phillips (International Journal of Integrated Care)
Introduction: Within the UK, NHS England has outlined the integral role of third sector organisations as a strategic partner in integrated care systems. This study sought to explore the embedding of a ‘new relationship’ in the co-design and delivery of ‘local’ services. Methods: Thirteen semi-structured interviews were conducted within a local authority area in England, with leaders from both the statutory and third sector. Interviews were analysed using framework analysis. Findings and Discussion: Findings suggest there is a need to go beyond the rhetoric in embedding a ‘new relationship’ with the third sector. More needs to be done to change the narrative as to how the third sector is perceived, for sectoral stereotypes to be dispelled, to move beyond tokenistic engagement and focus on how improving health can be tackled together. Whilst place-based forms of governance will differ, a greater understanding by the statutory sector of ‘local’ organisational and individual dynamics, capabilities and perspectives is paramount. Conclusion: The study concludes that policy narratives are not underpinned with institutional structures and mechanisms. Without a concerted effort and commitment to meaningful engagement, there is a risk that third sector goodwill dissipates in the face of the latest iteration of policy rhetoric.